Legal Principles of Agreements in Fixed-Term Employment Agreements (Study of PT Abc's Partnership Pattern Employment Agreements After Management Decision) - Kusumadewi, Dimitria Pawestri; Joesoef, Iwan Erar; Wati, Diani Sadia (Dinasti Research, 2025)
Employment relations in Indonesia are regulated in the 1945 Constitution and the Manpower Law, which guarantee workers' rights to employment and fair treatment. However, in practice, there has been a shift in terminology and work patterns, especially with the implementation of partnership patterns by companies to avoid employment obligations. This study highlights the implementation of partnership patterns at PT ABC which changes the status of warehouse workers to partners, thereby eliminating normative rights such as minimum wages, social security, and other benefits. Changes in terminology such as